MONITORING TEMPERATUR DAN KELEMBABAN BERBASIS IOT PADA SERVER - Iin Marlina; Adi Wibowo (Sienna, 2022)
Server is a place to store data and information that is owned so that it can be accessed by anyone and connected workstations from anywhere. If the server room gets too hot or too humid, it can cause your server to not work properly.air with too high humidity can damage the hardware on the server, for example, equipment can cause a short circuit caused by rust. The ideal humidity level for a server room is between 40 and 50%. As the humidity level increases, the amount of water vapor in the air increases. This can cause changes in vapor to liquid, electronic devices cannot be exposed to water. Many mistakes that are often made by server owners are by placing temperature and humidity detection sensors in the room, the temperature detection sensor should be placed in the rack of each server at each rack level, which is positioned at the front and back of the rack. The device that is commonly used in making Internet of Things applications is Arduino, Arduino is used as a link between the internet and sensors so that data from these sensors can be accessed. via the internet to set the behavior of specific equipment. In this study, Arduino was used because Arduino is an opensource device, the programming language used is C language and the Python programming language can also be used. From the availability of the library, there are many libraries that are ready and easy to use. Temperature and humidity detection in this study uses a DHT 11 temperature and humidity sensor connected to an Arduino device that is connected to the internet via a local network.